Marginal adaptation of lithium disilicate crowns obtained by scanning techniques (CAD/CAM): in vitro confocal microscopy analysis - de Freitas, Bruna Neves (2021)
Objective. This study aimed to evaluate lithium disilicate marginal adaption on crowns by scanning techniques (CAD/CAM), before and after crystallization, through confocal microscopy (CM) in vitro analysis. Methods. Sixteen polyurethane replicas were performed from tooth 1.4, of a typodont model, prepared for a full crown. The replicas were divided into two groups, according to the scanning technique: Indirect Technique (Group IND, n=08), where dental stone models were scanned with a laboratory scanner (inEos X5, Sirona Dental Systems) and Direct Technique (Group DIR, n=08), where typodont models were scanned with an intraoral scanner (CEREC BlueCam, Sirona Dental Systems). Then, the lithium disilicate crowns (IPS e.max CAD, Ivoclar Vivadent) were milled (inLab MC XL, Sirona Dental Systems) and adapted to the replicas. Marginal adaptation was evaluated with CM analysis before and after lithium disilicate crystallization. Data were analyzed with the Mann-Whitney, t test, and Wilconxon test (α=0.05). Results. There was a statistically significant difference in horizontal marginal adaptation between IND and DIR groups after crystallization (p=0.05). In IND group, the comparison of vertical marginal adaptation before and after crystallization showed a statistically significant difference (p=0.038). Conclusions. Lithium disilicate crowns obtained by direct scanning technique (CAD/CAD) showed less vertical marginal maladjustment. The crystallization stage affected the crown’s marginal adaptation.